Banana Corm Crackers as a Sustainable Food Innovation for Community Nutrition and Local Economic Empowerment - Janruel P. Tupas; Sharmaine P. Leones; Cherry-ann E. Gumabay; Maureen V. Brillantes; Jay-anne L. Banglay; Rency P. Bacud (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2025)
The utilization of banana corm for product diversification offers potential economic value, yet consumer preference remains a critical variable. This study aimed to determine the acceptability of Banana Corm Crackers in terms of three flavor variants (Lagundi, Pandan, and Turmeric), quality attributes (appearance, aroma, texture, and flavor), and packaging types (tub, transparent pastry box, and metallic stand-up pouch). Utilizing a descriptive-experimental research design, sensory evaluation was conducted with 30 Bachelor of Technical-Vocational Teacher Education (BTVTED) students majoring in Food and Service Management. Data were analyzed using Weighted Mean and Analysis of Variance (ANOVA). The results indicated that the Pandan flavor was the most preferred variant with a mean rating of 7.99 (